2020
DOI: 10.33182/ml.v17i2.927
|View full text |Cite
|
Sign up to set email alerts
|

Attracting High Skilled Individuals in the EU: The Finnish Experience

Abstract: The ageing population, demographic change and a lack of skilled labour in the EU are increasingly provoking governments to apply direct measures to aggressively recruit economic migrants, particularly high skilled individuals (HSIs). As most countries in the EU face similar challenges, attracting HSIs from the third countries are predominantly vital. One of the EU-wide programs to attract skilled professionals is the Blue Card program, which was introduced in 2009 as part of the European Council Direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Attracting high skilled individuals from third countries is of great importance because there is a lack of skilled labour in the EU. Lack of HSIs coupled with simultaneous demographic change is provoking governments into applying direct measures to recruit economic migrants [53]. In that regard, rich countries are developing measures for attracting HSIs.…”
Section: Labour Migration In the Eumentioning
confidence: 99%
“…Attracting high skilled individuals from third countries is of great importance because there is a lack of skilled labour in the EU. Lack of HSIs coupled with simultaneous demographic change is provoking governments into applying direct measures to recruit economic migrants [53]. In that regard, rich countries are developing measures for attracting HSIs.…”
Section: Labour Migration In the Eumentioning
confidence: 99%
“…Bianchi and Andrews (2015) also concluded that SMEs have benefited massively from the adoption of social media in order to ensure their market development by the availability of their brands on various social media platforms and subsequently changed consumption patterns. SME management use social media for various organizational purposes such as marketing, communication, sales, innovation, problem resolution, HRM, customer service, and above all technology and driving cultural changes (Ainin et al, 2015;Přívara et al, 2020;Hitka et al, 2021;Siekelova et al, 2021).…”
Section: Market Development and Expansionmentioning
confidence: 99%
“…The first is the increasing flows of skilled migrants, mostly from economically backward countries [8]. In this context, it can be stated that although the overall rate of migration from economically backward countries is very low, the relationship between GDP per capita and the rate of skilled emigrants is inverse [9]. In general, the poorer the country, the higher the emigration rate.…”
Section: Changes In the Characteristics Of Migrantsmentioning
confidence: 99%